Iatrogenic transfer metatarsalgia after hallux valgus surgery: a comprehensive treatment algorithm. Issue 9 (19th September 2022) - Chong, Xue Ling; Drittenbass, Lisca; Dubois-Ferriere, Victor; Assal, Mathieu
Abstract : Current literature has described many of the complications following hallux valgus surgery and their treatment options. Iatrogenic transfer metatarsalgia is a distinctive and challenging complication that has not been addressed in a comprehensive fashion yet. Iatrogenic transfer metatarsalgia may result from poor preoperative assessment, planning and/or surgical technique. We have classified the causes of iatrogenic transfer metatarsalgia based on a multiplanar assessment of the malalignment(s) and are recommending a comprehensive treatment algorithm to guide surgeons in addressing this complication. With this knowledge, surgeons may avoid potential pitfalls in the primary surgery that can result in iatrogenic transfer metatarsalgia and find the appropriate treatment option to correct them.